Bile acid metabolism in fish: disturbances caused by fishmeal alternatives and some mitigating effects from dietary bile inclusions. (2nd January 2020) - Romano, Nicholas; Kumar, Vikas; Yang, Gang; Kajbaf, Kimia; Rubio, Marina B.; Overturf, Ken; Brezas, Andreas; Hardy, Ronald
Abstract: Bile is a yellow‐green liquid produced in the liver from cholesterol and stored in the gallbladder of vertebrates. Bile improves the efficacy of lipid digestion by acting as an emulsifier and is essential in activating bile salt lipase, an enzyme that has broad substrate specificity. Bile improves the absorption of lipid soluble nutrients while also facilitating the excretion of cholesterol and toxic metabolites, particularly bilirubin. Dietary fishmeal alternatives often disturb bile acid status in fish resulting in either increased excretion/decreased intestinal reabsorption and/or decreased bile acid synthesis. Saponins and high molecular mass proteins are believed to contribute to altered bile acid status, which may reduce fish productivity. This situation can worsen with increased incorporations of plant‐based proteins in aquafeeds, but also may be mitigated by processing of fishmeal alternatives as well as the dietary inclusion of some bile acids/salts. This area of research will likely increase due to the roles dietary bile acids/salts can have on protecting digestive organs and improving nutrient utilization. This, however, depends on the bile type, level and fish species. This review discusses these aspects in regard to fish nutrition to help increase the inclusion of dietary fishmeal alternatives and thus enhance aquaculture sustainability.